The King Stayed Home: David with Bathsheba and Uriah - Hamman, Jaco J. (Pastoral psychology, 2023)
This paper explores the person of David (ca. 1010-1097 bce), king of Israel and Judah, especially his personal, familial, and professional undoing through his adultery with Bathsheba and the killing of her husband, Uriah the Hittite. After situating this event in the corpus of Davidic narratives, the paper examines David’s inner world—the David with Bathsheba—by drawing on the contribution of the British object relations theorist, W. R. D. "Ronald" Fairbairn. This paper argues that David relinquished his central ego to the castigations of an active inner critic and to the excitement of his libidinal ego. David, caught between these powerful forces, sabotaged his own reign, violated Bathsheba, became a murderer, and participated in his personal and familial demise. Men and contemporary leaders can learn from David’s undoing.